2021
DOI: 10.1186/s40538-020-00201-8
|View full text |Cite
|
Sign up to set email alerts
|

Coloured plastic mulches: impact on soil properties and crop productivity

Abstract: Mulches are materials applied in a soil surface for different roles and purposes. Plastic mulches with different colour have been developed and utilized in different crop production systems. Using coloured plastic mulches is mainly focused in modifying the radiation budget and decreasing the soil water loss. Besides, it helps to regulate soil temperature, water use efficiency, plant growth, yield, quality and weed and insect infestation. In this review, the knowledge and possible application of coloured plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 78 publications
1
43
0
1
Order By: Relevance
“…Mulching is an effective strategy that conserves soil moisture in oil palm plantation (Mohsen et al 2014 ; Iqbal et al 2020 ). Mulching enhances soil structure and water holding capacity (Jordan et al 2011 ; Iqbal et al 2020 ; Ngangom et al 2020 ; Amare and Desta 2021 ). Several agroecological and environment-friendly practices have been deployed in oil palm plantation to conserve soil, to minimise evapotranspiration, and to improve soil fertility (Nabara and Man 2018 ; Ahmed et al 2021 ).…”
Section: Oil Palm Adaptation and Mitigation To Climate Changementioning
confidence: 99%
“…Mulching is an effective strategy that conserves soil moisture in oil palm plantation (Mohsen et al 2014 ; Iqbal et al 2020 ). Mulching enhances soil structure and water holding capacity (Jordan et al 2011 ; Iqbal et al 2020 ; Ngangom et al 2020 ; Amare and Desta 2021 ). Several agroecological and environment-friendly practices have been deployed in oil palm plantation to conserve soil, to minimise evapotranspiration, and to improve soil fertility (Nabara and Man 2018 ; Ahmed et al 2021 ).…”
Section: Oil Palm Adaptation and Mitigation To Climate Changementioning
confidence: 99%
“…This experiment showed that due to the small plant canopy cover, white mulching film intercepts more solar radiation and has better light transmission than black mulching film. As a result, the cumulative temperature of the soil tillage layer of white mulching film is significantly higher than with black mulching film (Lu et al, 2016;Zhang et al, 2017a;Li et al, 2018a;Sun et al, 2018;Amare and Desta, 2021). The highest soil temperature period of the white mulching film was significantly higher than black mulching film at 16:00, during the maize seedling stage and jointing stage.…”
Section: Discussionmentioning
confidence: 93%
“…; Article no.AJAAR.71255 radiation into the mulch. Amare and Desta [29] asserted that black thick plastic mulch blocked solar radiation efficiently, minimized photosynthesis of weed, and caused low vegetative growth of weed. In contrast, transparent plastic mulch lets solar radiation pass through it, resulting in the growth and development of weed through increment in From the study, it can be concluded that both the atural and synthetic mulches had positive impacts on enhancing yield and yield attributing parameters of chili.…”
Section: Discussionmentioning
confidence: 99%